Nutritional Quality and Organoleptic Evaluation of Maize/ Orange Fleshed Sweet Potato Blend Complementary Food (London Journal of Research In Science: Natural and Formal, 2023)
Corn jellos (Agidi) is a gelatinous starchy food made by boiling a paste of fermented maize meal or flour. It can be substituted with legume, roots or seed at different constitution to boost it nutritional value. The maize and orange fleshed sweet potato (OFSP) were sourced from a local Market Ahia eke market Umuahia) and at National Root Crops Research Institute, Umudike. The maize was process into maize paste (MP) while the OFSP was prepared into flour, by soaking for 24hs, draining, sun drying for 48hrs, milling to obtain orange fleshed sweet potato flour (OFSPF). They were used to form blends at the following constitution: 1) at100% maize, (2)90%maize and 10%OFSP, (3)80%maize and 20%OFSP, (4)70%maize and 30%OFSP, and lastly(5)50%maize and 50%OFSP to get the following samples MSC1, MSC2, MSC3, MSC4 and MSC 5 respectively. The results showed that the that the proximate ranged from 15.74% to 16.45%, 0.2%3 to 0.28%, 18.40 to 22.13%, 0.24% to 0.31%, 3.89% to 4.90 %and 56.10% to 60.92% for moisture, ash, fat, fiber, protein and carbohydrate respectively. Organoleptic evaluation of the samples with parameter; appearance, taste, flavor, texture and general acceptability ranged from 6.00 to 8.75, 4.92 to 7.50, 5.42 to 8.00, 4.00 to 7.50, and 6.16 to 8.00 respectively. The vitamin A ranged from 151.10µ/100g to 193.50 µ/100g. Substitution of maize with orange fleshed sweet potato gave a better organoleptic properties in terms of appearance, flavor and general acceptability, while there was a progressive increase in all the vitamins evaluated across the samples. The inclusion of OFSP for the preparation of corn jellos is recommended to boost the nutritional content and the sensory qualities